(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Because of the developing enthusiasm for nanocomposites, a sub-atomic portrayal of thesematerials is fundamental for the comprehension of their properties and for the improvement of newmaterials. Spectroscopic systems that bring data at an atomic level are unavoidable when portrayingpolymers, fillers and composites. Chosen instances of the use of fluorescence, strong state atomicattractive reverberation (NMR), infrared and Raman spectroscopes, outline the capability of thesemethods for the investigation of the filler surface, the assessment of the condition of filler scattering inthe host network, the degree of communication between the polymer and the filler particles or theelements of polymer chains at the polymer–filler interface.